Perbedaan Efektivitas antara Sterilisasi Dialyzer secara Manual dan Otomatis di Rumah Sakit DR.Moewardi - Nindita, Dezca; Hudiyono, .; Sulaeman, Endang Sutisna (Nexus Biomedika, 2013)
Background: Dialyzer is a critical medical equipment having high risk of microorganism contamination. Because of economical reason, dialyzer reuse is performed as first choice in Indonesia. The making of dialyzer reuse starts from rinsing, priming test and sterilization itself. Sterilization method of dialyzer that has been carried out in Rumah Sakit Dr. Moewardi is manual and automatic sterilization. Method: This was an observational study using cross sectional design. Samples taken by consecutive sampling technique were collected from the last rinsing of NaCl right before the dialyzer was used. This NaCl samples were collected from dialyzer which were sterilized manually and automatically, each, 15 samples. The difference of posistive growth of bacteria cultures of both methods was analyzed by Chi square test, while the difference of the number of colony forming unit was analyzed by independent T test. Result: Fifteen samples of the last rinsing of NaCl from dialyzer sterilized manually showed there were 10 samples positive contaminated and 5 samples negative. While from dialyzer sterilized automatically showed there were 8 samples positive contaminated and 7 samples negative. All positive samples were contaminated by positive Gram bacteria. The statistical analyses showed no significant difference of both based on quality (p = 0.456) and quantity (p = 156). Conclusion: There was bacterial contamination as many as 10 samples (66.6%) of dialyzer which was sterilized manually and 8 samples (53.3%) of dialyzer which was sterilized automatically. There was no significant difference statistically on the effectiveness between manual and automatic sterilization. Keywords: dialyzer reuse, manual sterilization, automatic sterilization.